Adsorption and reaction of terephthaloyl chloride on Ag(111): X-ray photoelectron spectroscopy and density functional theory investigations - Schmid, Martin; Hieringer, Wolfgang; Schmitz, Christoph H.; Steinrück, Hans-Peter; Sokolowski, Moritz; Gottfried, Michael (Journal of Physical Chemistry C, 2011)
The adsorption and reaction of terephthaloyl chloride (TPC) on a Ag(111) surface was investigated with X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) calculations. Below 120 K, TPC forms multilayers without reacting with the Ag(111) substrate. Multilayer desorption starts above 120 K and is accompanied by a chemical reaction between the TPC molecules and the Ag surface. This reaction involves scission of the carbon-chlorine bond, resulting in the formation of adsorbed chlorine atoms and a p-phenylene dicarbonyl (pPDC) species. This molecular fragment is stable at room temperature and does not undergo further decomposition, presumably due to stabilization by adsorbate-substrate interactions and/or oligomerization. The DFT calculations confirm that pPDC is a possible intermediate or final reaction product and show that the two carbonyl C atoms form covalent bonds to the Ag substrate. © 2011 American Chemical Society.

Adsorption of cobalt (II) octaethyIporphyrin and 2H-octaethylporphyrin on Ag(111): New insight into the surface coordinative bond - Bai, Yun; Buchner, Florian; Kellner, Ina; Schmid, Martin; Vollnhals, Florian; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (New Journal of Physics, 2009)
The adsorption of cobalt (II) octaethylporphyrin (CoOEP) and 2H-octaethylporphyrin (2HOEP) on Ag(111) was investigated with scanning tunneling microscopy (STM) and photoelectron spectroscopy (XPS/UPS), in order to achieve a detailed mechanistic understanding of the surface chemical bond of coordinated metal ions. Previous studies of related systems, especially cobalt (II) tetraphenylporphyrin (CoTPP) on Ag(111), have revealed adsorptioninduced changes of the oxidation state of the Co ion and the appearance of a new valence state. These effects were attributed to a covalent interaction of the Co ion with the silver substrate. However, recent studies show that the porphyrin ligand of adsorbed CoTPP undergoes a pronounced saddle-shape distortion, which could alter the electronic structure and thus provide an alternative explanation for the new valence state previously attributed to the formation of a surface coordinative bond. With the octaethylporphyrins investigated here, which were found to adsorb in a flat, undistorted conformation on Ag(111), the effects of geometric distortion can be separated from those of the electronic interaction with the substrate. The CoOEP monolayer gives rise to an adsorption-induced shift of the Co 2p signal (-1.9 eV relative to the multilayer), a new valence state at 0.6 eV below the Fermi energy, and a work-function shift of -0.84eV (2HOEP: -0.44eV) relative to the clean surface. Comparison with data for the distorted CoTPP confirms the existence of a covalent ion-surface interaction that is insensitive to the conformation of the ligand. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.

A new asymmetric Pseudo-Voigt function for more efficient fitting of XPS lines - Schmid, Martin; Steinrück, Hans-Peter; Gottfried, J. Michael (Surface and Interface Analysis, 2014)
Asymmetric peak profiles for the application in spectroscopy can be obtained in a simple way by substituting the usually constant full width at half maximum parameter in Pseudo-Voigt functions with an energy-dependent expression, for instance of sigmoidal shape. While this approach has been successfully applied to vibrational spectra, we find that the resulting curves are less suitable for least-squares fits of X-ray photoelectron spectroscopy (XPS) data. However, if one additionally allows a variable displacement of the sigmoidal step relative to the peak, excellent fitting results can be obtained. We demonstrate the applicability of our extended approach on several inherently asymmetric XPS lines, i.e. the C 1s signal of graphite and CH/Pd(100), the 3d-3d doublet of palladium, and the 4f-4f doublet of platinum. Comparison of the corresponding fit results with the results obtained by the application of more elaborate, theory-based line profiles (Doniach-Šunjić and Mahan functions) shows that the modified Pseudo-Voigt function gives practically identical results in terms of peak shape and area, while requiring much less computational effort since no convolution procedures are required for its calculation. Thus, this function is most suitable for application in one of the following situations: (i) the peak shape of a given signal is known but cannot be calculated with ease, and (ii) the theoretical peak shape is not (yet) known, however, one wants to perform a first quantitative screening of the data at issue. © 2014 John Wiley & Sons, Ltd.

A new asymmetric Pseudo-Voigt function for more efficient fitting of XPS lines (vol 46, pg 505, 2014) - Schmid, Martin; Steinrück, Hans-Peter; Gottfried, Michael (Surface and Interface Analysis, 2015)

Coordination and metalation bifunctionality of Cu with 5,10,15,20-tetra(4- pyridyl)porphyrin: Toward a mixed-valence two-dimensional coordination network - Li, Yang; Xiao, Jie; Shubina, Tatyana; Chen, Min; Shi, Ziliang; Schmid, Martin; Steinrück, Hans-Peter; Gottfried, J. Michael; Lin, Nian (Journal of the American Chemical Society, 2012)
We investigated the coordination self-assembly and metalation reaction of Cu with 5,10,15,20-tetra(4-pyridyl)porphyrin (2HTPyP) on a Au(111) surface by means of scanning tunneling microscopy, X-ray photoelectron spectroscopy, and density functional theory calculations. 2HTPyP was found to interact with Cu through both the peripheral pyridyl groups and the porphyrin core. Pairs of pyridyl groups from neighboring molecules coordinate Cu(0) atoms, which leads to the formation of a supramolecular metal-organic coordination network. The network formation occurs at room temperature; annealing at 450 K enhances the process. The interaction of Cu with the porphyrin core is more complex. At room temperature, formation of an initial complex Cu(0)-2HTPyP is observed. Annealing at 450 K activates an intramolecular redox reaction, by which the coordinated Cu(0) is oxidized to Cu(II) and the complex Cu(II)TPyP is formed. The coordination network consists then of Cu(II) complexes linked by Cu(0) atoms; that is, it represents a mixed-valence two-dimensional coordination network consisting of an ordered array of Cu(II) and Cu(0) centers. Above 520 K, the network degrades and the Cu atoms in the linking positions diffuse into the substrate, while the Cu(II)TPyP complexes form a close-packed structure that is stabilized by weak intermolecular interactions. Density functional theory investigations show that the reaction with Cu(0) proceeds via formation of an initial complex between metal atom and porphyrin followed by formation of Cu(II) porphyrin within the course of the reaction. The activation barrier of the rate limiting step was found to be 24-37 kcal mol depending on the method used. In addition, linear coordination of a Cu atom by two CuTPyP molecules is favorable according to gas-phase calculations. © 2012 American Chemical Society.

Interfacial coordination interactions studied on cobalt octaethylporphyrin and cobalt tetraphenylporphyrin monolayers on Au(111) - Bai, Yun; Sekita, Michael; Schmid, Martin; Bischof, Thomas; Steinrück, Hans-Peter; Gottfried, Michael (Physical Chemistry Chemical Physics, 2010)
Monolayers and multilayers of cobalt octaethylporphyrin (CoOEP), cobalt tetraphenylporphyrin (CoTPP) and the corresponding free-base porphyrins 2HOEP and 2HTPP on an Au(111) surface were investigated with X-ray and UV photoelectron spectroscopy (XPS and UPS). For CoTPP and CoOEP monolayers, the XP spectra show a characteristic splitting of the Co 2p signal, which suggests that only a fraction of the Co ions forms coordinative bonds to the Au(111) surface, while the others interact more weakly. This is a remarkable difference to previous results for CoOEP and CoTPP on Ag(111), where all Co ions in the monolayer were found to interact strongly and uniformly with the silver surface. Presumably, the lateral structural and electronic inhomogeneities of the reconstructed Au(111) surface are responsible for the more complex interaction behaviour on the gold surface. UP spectra of CoOEP and CoTPP monolayers show a new electronic state around 0.3 eV below the Fermi energy (E), i.e., at lower binding energy than in the case of Ag(111), where a strong signal appeared at 0.6 eV below E. In contrast, the free-base porphyrins 2HOEP and 2HTPP show no additional valence states in the monolayer, indicating that the Co ion plays a central role in the electronic interaction between the metal complexes and the substrate. These results have important implications for metal/organic interfaces in organic electronics or photovoltaic devices based on π-conjugated semiconducting metal complexes, because the character of the chemical bond at the interface determines important parameters such as charge injecting rates. © 2010 the Owner Societies.

Interfacial interactions of iron(II) tetrapyrrole complexes on Au(111) - Schmid, Martin; Zirzlmeier, Johannes; Steinrück, Hans-Peter; Gottfried, J. Michael (Journal of Physical Chemistry C, 2011)
The electronic structure of monolayers of iron(II) phthalocyanine (FePc), iron(II) octaethylporphyrin (FeOEP), and iron(II) tetraphenylporphyrin (FeTPP), adsorbed on Au(111), was examined with X-ray and UV photoelectron spectroscopy (XPS/UPS). Comparison of the Fe 2p signals of FePc multilayers and monolayers revealed an additional component in the monolayer signal with a binding energy characteristic of Fe(0). This component accounts for ∼20% of the integral Fe 2p intensity, in agreement with previous observations on cobalt porphyrins on Au(111). The partial modification of the Fe 2p states suggests a laterally inhomogeneous interaction of the adsorbed molecules with the metal surface and is possibly related to the complex, reconstructed Au(111) surface morphology. Similar results obtained for FeTPP and FeOEP monolayers indicate that this effect is independent from the structure of the peripheral substituents on the core porphin moiety. The UP spectra of FePc and FeTPP monolayers show further indications for a substrate-molecule interaction mediated by the central Fe atom. In addition, FePc, FeTPP, and 2HTPP monolayers lead to a complete depopulation of the Shockley surface state of the clean Au(111) surface. © 2011 American Chemical Society.

Ionic liquid based model catalysis: Interaction of [BMIM][Tf2N] with Pd nanoparticles supported on an ordered alumina film - Sobota, Marek; Schmid, Martin; Happel, Markus; Amende, Maximilian; Maier, Florian; Steinrück, Hans-Peter; Paape, Natalia; Wasserscheid, Peter; Laurin, Mathias; Gottfried, Michael; Libuda, Jörg (Physical Chemistry Chemical Physics, 2010)
Towards a better understanding of novel catalytic materials consisting of supported noble metal catalysts modified by an ionic liquid (IL) film, we have performed a study under ultrahigh-vacuum (UHV) conditions. The model surface consists of Pd nanoparticles grown in UHV on an ordered alumina film on NiAl(110). Thin films of the room temperature IL 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][TfN] are deposited onto this surface by means of physical vapor deposition (PVD). The interaction of the IL with clean and CO-covered Pd/AlO/NiAl(110) at 300 K and the thermal behavior of the deposited IL films on Pd/AlO /NiAl(110) are investigated by time-resolved infrared reflection absorption spectroscopy (TR-IRAS) and X-ray photoelectron spectroscopy (XPS). At 300 K, the IL adsorbs molecularly both onto the Pd particles and onto the alumina. The IR spectra suggest that the [TfN] anions interact with Pd sites preferentially via the sulfonyl groups. CO pre-adsorbed on the Pd particles is partially displaced by the IL, even at 300 K, and only the part of CO adsorbed onto hollow sites on (111) facets of the Pd particles remains in place. Upon heating to temperatures higher than the desorption temperature of the IL (>400 K), molecular desorption of the IL competes with decomposition. The decomposition products, atomic species and small fragments, remain preferentially adsorbed onto the Pd nanoparticles and strongly modify their surface properties. Most of the decomposition products originate from the [BMIM] cations, whereas the [TfN] anions desorb for the most part. © 2010 the Owner Societies.

Surface polymerization of poly(p -phenylene-terephthalamide) on Ag(111) investigated by X-ray photoelectron spectroscopy and scanning tunneling microscopy - Schmitz, Christoph H.; Schmid, Martin; Gärtner, Stefan; Steinrück, Hans-Peter; Gottfried, Michael; Sokolowski, Moritz (Journal of Physical Chemistry C, 2011)
The formation of poly(p-phenylene-terephthalamide) (PPTA) by surface-assisted polymerization of terephthaloyl chloride (TPC) and p-phenylenediamine (PPD) on Ag(111) has been studied by X-ray photoelectron spectroscopy (XPS) and scanning tunneling microscopy (STM). Analysis of the XPS data reveals that the polymer is formed in the (sub-) monolayer regime already at room temperature. Upon vacuum deposition of TPC onto the single-crystal surface, the carbon-chlorine bond is cleaved, and the polymerization proceeds via a p-phenylene dicarbonyl species, which is presumably surface stabilized. This contrasts the reaction mechanism in solution, where the chlorine atom is expelled after a nucleophilic attack by the amine group. Annealing of the sample leads to desorption of residual PPD monomers, lateral ordering of the polymer chains, and further progress of the polymerization that can be followed by XPS. The chain length distribution of the polyamide, as extracted from the XP spectra, is consistent with the typical chain lengths found in STM images. © 2011 American Chemical Society.

The electronic structure of cobalt(II) phthalocyanine adsorbed on Ag(111) - Schmid, Martin; Kaftan, Andre; Steinrück, Hans-Peter; Gottfried, Michael (Surface Science, 2012)
The electronic states of submonolayers and multilayers of cobalt(II) phthalocyanine (CoPc) adsorbed on Ag(111) were examined with photoelectron spectroscopy to obtain insight into the details of the substrate-adsorbate interaction. UV photoelectron spectroscopy (UPS) reveals the presence of two interaction-related valence states in the direct vicinity of the Fermi edge, in agreement with previous DFT calculations. X-ray photoelectron spectra indicate that the substrate-adsorbate interaction results in transfer of electron density from the substrate to the Co(II) ion. Substantial changes in the Co 2p multiplet structure, a spectral pattern induced by the open-shell character of the central Co(II) ion, indicate a complete quenching of the molecular spin. While pristine CoPc molecules are paramagnetic with S = 1/2, molecules in direct contact to the Ag(111) substrate appear to be in a diamagnetic state. © 2012 Elsevier B.V. All rights reserved.

Toward well-defined metal-polymer interfaces: Temperature-controlled suppression of subsurface diffusion and reaction at the calcium/poly(3- Hexylthiophene) interface - Bebensee, Fabian; Schmid, Martin; Steinrück, Hans-Peter; Campbell, C. T.; Gottfried, Michael (Journal of the American Chemical Society, 2010)
The thickness of the reaction zone at the interface between calcium and regioregular poly(3-hexylthiophene), which is one of the best performing metal/polymer combinations in photovoltaic devices, depends critically on the temperature of the polymer during the initial phase of metal deposition. It is shown that deposition at 130 K reduces the thickness of the reaction zone, an effect that also persists after warming to room temperature. © 2010 American Chemical Society.